The Application of the “Law of Crime Concentration” to Terrorism: the Jerusalem Case Study - Perry, Simon (Journal of quantitative criminology, 2020)
One of the areas in terrorism that has not been adequately examined, is the geographic concentration of terror attacks in a city’s micro places. The literature related to the geographical distribution of terror generally focuses on macro places: continents, countries, and regions. In contrast, in the study of ordinary crime, significant studies have been conducted on the distribution of crime in micro-places “hot spots”. The findings of these studies have great significance when adopting models of law enforcement. This study examines whether there is a concentration of terror attacks in a limited number of hot spots that are stable over time.